The impact of compensated and decompensated cirrhosis on the postoperative outcomes of patients undergoing hernia repair: a propensity score-matched analysis of 2011–2017 US hospital database. Issue Volume 33:Issue S1(2021) (30th December 2021) - Lee, David Uihwan; Hastie, David Jeffrey; Lee, Ki Jung; Hongyuan Fan, Gregory; Ann Addonizio, Elyse; Kwon, Jean; Karagozian, Raffi
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and aims: Since there is clinical overlap between populations with cirrhosis and those who require hernia repair (i.e. due to stretching of abdominal walls), we systematically evaluate the effects of cirrhosis on post-hernia repair outcomes. Methods: 2011–2017 National Inpatient Sample was used to identify patients who underwent hernia repair (included: inguinal, umbilical, and other abdominal hernia repairs). The population was stratified into those with compensated cirrhosis (CC), decompensated cirrhosis (DC), and no cirrhosis; hepatic decompensation was defined as those with portal hypertension, ascites, and varices. The propensity score was used to match the no-cirrhosis controls to CC and DC using the 1:1 nearest neighbor mechanism. Endpoints included mortality, length of stay, costs, and complications. Results: Postmatch, there were 392/446 CC/DC with equal number controls in those undergoing inguinal hernia repair, 714/1652 CC/DC with equal number controls in those undergoing umbilical hernia repair, and 784/702 CC/DC. In multivariate, for inguinal repair, there was no difference in mortality [CC vs. no-cirrhosis aOR 2.61, 95% confidence interval (CI) 0.50–13.52; DC vs. no-cirrhosis: aOR 1.75, 95% CI 0.84–3.63]. For umbilical repair, there was no difference in mortality for CC vs. no-cirrhosis: aOR 0.94, 95% CI 0.36–2.42); however, DC had higher mortality (aOR 2.86, 95% CI 1.76–4.63) when comparing DC vs. no-cirrhosis. For other abdominal repairs, there was no difference in mortality for CC vs. no-cirrhosis (aOR 1.10, 95% CI 0.54–2.23); however, DC had higher mortality ( P < 0.001, aOR 2.58, 95% CI 1.49–4.46) when comparing DC vs. no-cirrhosis. Conclusion: This study demonstrates that the presence of DC affects postoperative survival in patients undergoing umbilical or other abdominal hernia repair surgery.